Lack of isocitrate lyase in Chlamydomonas leads to changes in carbon metabolism and in the response to oxidative stress under mixotrophic growth. (7th January 2014) - Plancke, Charlotte; Vigeolas, Helene; Höhner, Ricarda; Roberty, Stephane; Emonds‐Alt, Barbara; Larosa, Véronique; Willamme, Remi; Duby, Franceline; Onga Dhali, David; Thonart, Philippe; Hiligsmann, Serge; Franck, Fabrice; et al.
Summary Isocitrate lyase is a key enzyme of the glyoxylate cycle. This cycle plays an essential role in cell growth on acetate, and is important for gluconeogenesis as it bypasses the two oxidative steps of the tricarboxylic acid (TCA) cycle in which CO2 is evolved. In this paper, a null icl mutant of the green microalga Chlamydomonas reinhardtii is described. Our data show that isocitrate lyase is required for growth in darkness on acetate (heterotrophic conditions), as well as for efficient growth in the light when acetate is supplied (mixotrophic conditions). Under these latter conditions, reduced acetate assimilation and concomitant reduced respiration occur, and biomass composition analysis reveals an increase in total fatty acid content, including neutral lipids and free fatty acids. Quantitative proteomic analysis by 14N/15N labelling was performed, and more than 1600 proteins were identified. These analyses reveal a strong decrease in the amounts of enzymes of the glyoxylate cycle and gluconeogenesis in parallel with a shift of the TCA cycle towards amino acid synthesis, accompanied by an increase in free amino acids. The decrease of the glyoxylate cycle and gluconeogenesis, as well as the decrease in enzymes involved in β–oxidation of fatty acids in the icl mutant are probably major factors that contribute to remodelling of lipids in the icl mutant. These modifications are probably responsible for the elevation of the response to oxidative stress, with significantly augmented levels and activities of superoxide dismutase and ascorbate peroxidase, and increased resistance to paraquat.